Languages Attitudes Towards Written Alay Variety in Facebook Interaction - Widya Astuti (Passage, 2013)
This research paper entitled Language Attitudes towards Written ‘Alay’ Variety in Facebook Interaction aims to reveal the use of the alay variety in Facebook media and the attitudes developed by users and ex-users of the variety. The study employs a descriptive method to describe and interpret the data. The study reveals that the realization of written alay variety in Facebook covers two broad categories, namely spelling and writing that involves a mix of capitals and punctuations. The spelling modifications in written alay variety were found to be in four different cases, spelling shift, spelling addition, spelling deletion, contraction, and irregular spelling modification. Related to language attitudes toward the written alay variety, users and ex-users develop different attitudes towards the use of alay variety. Users tend to have more neutral attitudes with the use of alay variety, they develop more positive attitudes towards the variety. In contrast, most ex-users react negatively towards the use of alay variety as they consider the variety to have a low prestige or status and is not a proper variety to use. Keywords: alay, alay variety, spelling, modification, language attitudes